Demographic and clinical factors associated with suicide in gastric cancer in the United States - Bowden, Mallory B.; Walsh, Nathaniel J.; Jones, Andrew J.; Talukder, Asif M.; Lawson, Andrew G.; Kruse, Edward J. (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
While increased suicidal tendencies among cancer patients have been well documented, there has been no speci c examination of suicide and gastric cancer. The purpose of this study is to characterize suicide incidence among patients diagnosed with gastric cancer from 1973 to 2013 and identify variables associated with higher suicide rates. Patients with gastric cancer were identi ed in the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute. The study included clinical and demographic data from 1973 to 2013. Standardized mortality ratios (SMRs) and 95% confidence intervals (95% CIs) were calculated. Comparisons with the general US population were based on mortality data collected by the Centers for Disease Control and Prevention’s National Center for Injury Prevention and Control using the Web-based Injury Statistics Query and Reporting System. Multivariable logistic regression models generated odds ratios (ORs) to assess factors associated with increased suicide in gastric malignancy. There were 210 suicides for patients with gastric cancer (SMR, 3.21; 95% CI: 2.80–3.67). Female gender (SMR 8.54), White race (SMR 4.08), age ≤39 years (SMR 3.06), and age 70–79 years (SMR 2.90), were found to be signi cant for an increased incidence of suicide compared with the general population. There was not a statistically signi cant relationship between suicide and marital status, income, mode of radiation therapy, and the role of surgical intervention. Approximately 77% of deaths by suicide occurred within the first year following diagnosis. Female gender, White race, age ≤39 years, and age 70–79 years are factors associated with increased risk of suicide in patients with gastric cancer. These results, coupled with further studies and analyses, will be used to formulate a comprehensive suicide risk factor scoring system for screening all cancer patients.